POETICS OF HISTORICAL PROSE WORKS - Kholjigitova Gulbahor Toshtemir qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: The poetics of historical prose works is a system of works that express historical events, persons and times through art and literature. Historical prose includes historical facts, events and persons, and describes them in an artistic style. These works try to convey the historical atmosphere, spirit and emotions to the reader or listener by incorporating the historical truth into an artistic form. The poetics of historical prose includes the artistic form, style, image and means of expression of the works. This article examines the poetics of historical prose works, its features, artistic style, and methods of artistic expression of historical events.